AN EXTRAPOLATORY QUADRATURE RULEFOR ANALYTIC FUNCTIONS - Mohanty, P.M.; Acharya, M. (International Journal of Research -GRANTHAALAYAH, 2016)
A quadrature rule for the numerical evaluation of integrals of analytic functions along directed line segments in the complex plane has been formulated using the transformed rule based on Gauss Legendre two point quadrature formulas and an interpolatory three point rule. The degree of precision has been increased from five to seven